Gereja Bagi Dunia: Rahmat dan Kewajiban Umat Beriman - Sudhiarsa, Raymundus I Made (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2015)
This article argues that the Second Vatican Council has recognised the missionary nature of the entire Church (AG, 2). Carrying out the mission means that the Church (clergy as well as lay people) is enthusiatically responding signs of the times in close collaboration with peoples of good will. Time and again, following the decree of Ad Gentes, the Catholic Church expresses its missionary identity in renewed ways in its mission documents. The present article starts with Ad Gentes (The Church’s missionary activity, 1965) and goes through Evangelii Nuntiandi (Evangelization in the modern world, 1975), Redemptoris Missio (The permanent validity of the Church’s missionary mandate, 1990), and Evangelii Gaudium (The proclamation of the gospel in today’s world, 2013). The Church has been moving out from the position of ‘maintenance’ to ‘mission’, as Pope Francis formulates in this words: “The word of God constantly shows us how God challenges those who believe in him ‘to go forth’” (EG, 20). Accordingly every Christian is expected to ‘go forth’ due to his/her baptism, because the Church itself is ‘a community of missionary disciples’ (EG, 24.40.120).